2017
DOI: 10.1016/j.cattod.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Dry reforming of CH4 on Co/Al2O3 catalysts reduced at different temperatures

Abstract: Keywords:Dry reforming of CH4 Co/Al2O3 catalyst XPS of Co/Al2O3 Surface carbon a b s t r a c t The reforming of methane with carbon dioxide has been investigated at 773 K on 10% Co/Al 2 O 3 reduced at different temperatures up to 1173 K. The catalysts were characterized by BET, TPR, XRD and XPS methods. TPR and XPS results revealed that during the pre-treatment of the catalysts the Co only partially reduced. The reduction degree and the amount of the structured metallic cobalt increased with the reduction temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 43 publications
(57 reference statements)
2
24
0
1
Order By: Relevance
“…[18] The result was accordance with our observation that structural variation from b-Co to a-Co could occuru nder the reaction conditions. [18] The result was accordance with our observation that structural variation from b-Co to a-Co could occuru nder the reaction conditions.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…[18] The result was accordance with our observation that structural variation from b-Co to a-Co could occuru nder the reaction conditions. [18] The result was accordance with our observation that structural variation from b-Co to a-Co could occuru nder the reaction conditions.…”
Section: Introductionsupporting
confidence: 92%
“…As for 11.1-Co@SiO 2 -6.0 ( Figure 5a), besides the peaks at 778.0 and 780.1 eV,a dditional peaks at 782.9 and 785.7 eV appear, and they can be attributed to the Co species with mediumo r strong core-shell interaction, respectively.C learly,t he XPS data are compiled well with the H 2 -TPR results. [18] In the currents tudy,t he Co 0 fraction increases with increasing core particle size, and this is expected because the bulky Co 3 O 4 cores are readily reduced asi llustrated in the H 2 -TPR investigation. Horvµth et al reported that the Co 0 fraction was only 0.57 even if the Co 3 O 4 / Al 2 O 3 precursor was subjected to ap re-reductiona t9 00 8C.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 82%
“…Recent studies on the application of common support materials for Co and Ni catalysts in dry reforming have demonstrated that the performance of support decreased in the order of Al 2 O 3 >MgO>SiO 2 >ZrO 2 >TiO 2 . The superior activity of Al 2 O 3 and MgO is most likely resulted from their strong metal‐support interaction, providing several advantages such as improve catalyst stability, prevent active metal sintering and promote CO 2 conversion . Particularly, Co supported on Al 2 O 3 catalysts have constituted an important class of catalytic materials and have been widely examined owing to their high abundancies, excellent catalytic activities, and good resistance towards carbon deposition .…”
Section: Introductionmentioning
confidence: 99%
“…[1,7,20,21] The superior activity of Al 2 O 3 and MgO is most likely resulted from their strong metal-support interaction, providing several advantages such as improve catalyst stability, prevent active metal sintering and promote CO 2 conversion. [6,7,20,22,23] Particularly, Co supported on Al 2 O 3 catalysts have constituted an important class of catalytic materials and have been widely examined owing to their high abundancies, excellent catalytic activities, and good resistance towards carbon deposition. [24] Al 2 O 3 is able to induces high dispersion of the Co metal to prevent the sintering of active sites, thereby preserving the activity of Co. [25,26] With reference to Co/Al 2 O 3 catalysts, different preparation methods and metal loadings have been examined to yield catalysts with diverse structures and reactivities toward dry reforming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation